2015
DOI: 10.1039/c4dt03377a
|View full text |Cite
|
Sign up to set email alerts
|

Two novel octamolybdate nanoclusters as catalysts for dye degradation by air under room conditions

Abstract: Two novel inorganic-organic hybrid materials, namely, (NH4)2CuMo8O26(C10H8N2)2 (1) and Mo8O26(C10H10N2)2(C10H8N2)·2(H2O) (2) have been synthesized based on β-octamolybdate cluster and 4,4'-bipyridine (4,4'-bpy) ligand under solvothermal conditions. Their structures have been determined by single-crystal X-ray diffraction analyses and characterized by FT-IR, atomic absorption spectroscopy, powder X-ray diffraction (PXRD) and thermogravimetric analysis (TGA). In addition, microcrystals of 1 were used to synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The Mo center exhibits a six‐coordinated geometry and is surrounded by one N atom from 4,4′‐bpy ligand (Mo−N1, 2.422(3)), one terminal oxygen (Mo−O1, 1.698(3)) and four bridging μ 2 ‐O oxygens (Mo−O3, 2.098(3); Mo−O2, 1.993(3); Mo−O2 i , 1.786(3); Mo−O3 ii , 1.753(3); (symmetry code: (i) 1‐x, −0.5+y, −0.5‐z; (ii) −0.5+x, y, −0.5‐z)). The bond distances are in the range of those reported in the literature …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The Mo center exhibits a six‐coordinated geometry and is surrounded by one N atom from 4,4′‐bpy ligand (Mo−N1, 2.422(3)), one terminal oxygen (Mo−O1, 1.698(3)) and four bridging μ 2 ‐O oxygens (Mo−O3, 2.098(3); Mo−O2, 1.993(3); Mo−O2 i , 1.786(3); Mo−O3 ii , 1.753(3); (symmetry code: (i) 1‐x, −0.5+y, −0.5‐z; (ii) −0.5+x, y, −0.5‐z)). The bond distances are in the range of those reported in the literature …”
Section: Resultssupporting
confidence: 94%
“…Sonochemical process has been widely utilized as a facile and economical method to produce nanostructured coordination polymers . In this concept, our research group reported the synthesis of (NH 4 ) 2 CuMo 8 O 26 (4,4′‐bpy) 2 nanosized coordination polymer through an ultrasound‐assisted top‐down method and investigated the enhanced catalytic activity of the polymer in nanoscale …”
Section: Introductionmentioning
confidence: 99%
“…(NH 4 ) 6 The powder X-ray diffraction (PXRD) patterns were obtained using a Philips PW1800 diffractometer with Cu Kα radiation (λ = 1.5406 Å). FT-IR spectra of the samples were recorded with a Bruker Enquinox 55 spectrometer equipped with a single reflection diamond ATR system.…”
Section: Methodsmentioning
confidence: 99%
“…In the FT-IR spectrum of nanosized 1, shown in Fig. 6, the peaks at 931-493 cm -1 can be assigned to the ν(Mo=O) and ν(Mo-O-Mo) vibrations [6]. The FT-IR spectrum (Fig.…”
Section: Nanoparticles Ofmentioning
confidence: 98%
“…However, octamolybdate cluster based solids have been used earlier for dye adsorption 34 and degradation properties. 35,36 The intriguing layer-like structure, porosity and acidic nature of title compound motivated us to use it for dye uptake. Methylene Blue (MB) and Basic Violet 1 (BV1) were tried as both have basic nature.…”
Section: Dye Adsorption Studiesmentioning
confidence: 99%